Watershed Infarcts in Transient Ischemic Attack/Minor Stroke With ≥50% Carotid Stenosis: Hemodynamic or Embolic? - Moustafa, Ramez R.; Izquierdo-Garcia, David; Jones, P. Simon; Graves, Martin J.; Fryer, Tim D.; Gillard, Jonathan H.; Warburton, Elizabeth A.; Baron, Jean-Claude (Stroke (1970), 2010)
Background and Purpose— Watershed ischemia is a significant cause of stroke in severe carotid disease, but its pathophysiology is unsettled. Although hemodynamic compromise has long been regarded as the main mechanism—particularly with deep watershed infarction—there is some contradictory evidence from clinical and pathological studies for a role of microembolism, thought to result from plaque inflammation. However, no study so far has directly addressed these conflicting scenarios. Methods— In 16 consecutive patients with recent transient ischemic attack/minor stroke and ipsilateral 50% to 99% carotid stenosis, we prospectively obtained (1) plaque inflammation mapping with 18 F fluorodeoxyglucose positron emission tomography; (2) brain MRI and perfusion MR; and (3) transcranial Doppler detection of microembolic signals (MES). Patients were excluded if on dual antiplatelets or with a potential cardiac source of emboli or contralateral MES. Results— We found the expected significant relationship between (1) degree of stenosis and severity of distal hemodynamic impairment in the watershed areas; and (2) degree of in vivo plaque inflammation and rate of MES/hr. Deep watershed infarcts were present in 8 patients and MES in 8 (3 with both). There was no systematic association between the presence of deep watershed infarcts and either hemodynamic impairment or MES, but deep watershed infarcts were present only when either hemodynamic impairment or MES was present ( P =0.01). Conclusion— This pilot study supports the idea that in symptomatic carotid disease, deep watershed infarcts result either from hemodynamic impairment secondary to severe lumen stenosis or from microembolism secondary to plaque inflammation. There was no direct evidence that both mechanisms act in synergy.